2003
DOI: 10.1046/j.1524-4733.2003.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Drug Delivery for CHOP, COP/CVP, and Fludarabine: An International Assessment

Abstract: Costs of drug administration are a major driver for total direct treatment costs in the treatment of relapsed low-grade NHL and are at least as important as drug acquisition costs. Drug administration practices, in terms of inpatient or outpatient treatment, are a major factor in determining overall direct costs. Therapeutic strategies, which offer shortened treatment duration and/or a simple mode of administration, are likely to be economically attractive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
5
1
1
Order By: Relevance
“…Herold et al [12, 13] reported costs for Canada, Germany and Italy, and it is difficult to compare these findings with our own. Sweetenham et al [15] reported the findings of a UK cost-minimization analysis comparing CHOP, fludarabine and rituximab with costs (in 1998) calculated from the perspective of the hospital.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Herold et al [12, 13] reported costs for Canada, Germany and Italy, and it is difficult to compare these findings with our own. Sweetenham et al [15] reported the findings of a UK cost-minimization analysis comparing CHOP, fludarabine and rituximab with costs (in 1998) calculated from the perspective of the hospital.…”
Section: Discussioncontrasting
confidence: 61%
“…Previous studies have considered the cost of therapies for indolent follicular NHL [12,13,14,15]. Based on a retrospective chart review of relapsed follicular NHL patients in Canada, Germany and Italy, Herold et al [12, 13] reported the average cost of treatment per patient for fludarabine, CVP and CHOP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…drug administration is a major cost driver for overall treatment costs [5,6]. The combination of a simplified administration and favorable clinical results may lead to an economic benefit with capecitabine vs. conventional 5-FUbased treatments [7].…”
Section: Introductionmentioning
confidence: 99%
“…Studien in anderen onkologischen Indikationen haben gezeigt, dass die i. v.-Applikation von Chemotherapeutika einen wichtigen Faktor für die gesamten Behandlungskosten darstellt [7], [8]. Die Kombination einer einfachen und patientenfreundlichen Applikationsform mit den positiven klinischen Resultaten könn-te auch in einen ökonomischen Vorteil für Capecitabin gegenüber der konventionellen Fluoropyrimidin-Therpie münden [9].…”
Section: Introductionunclassified